Editorial Board - Surbakti, Tukiran (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2022)
This section consists of Cover Page, Editorial Board Page, Peer Reviewer Page, Table of Content Page and Preface Page